British Prime Ministers from Walpole to Salisbury - Leonard, R. L. (Richard Lawrence), author.
1 online resource
Keywords: "Dick Leonard's British Prime Ministers from Walpole to Salisbury surveys the lives and careers of all the 32 Prime Ministers from Sir Robert Walpole (1721-42) to Archibald Philip Primrose, 5th Earl of Rosebery (1894-95) in 32 succinct, informative and entertaining chapters. Bringing to life the political achievements and personal idiosyncrasies of Britain's rulers over the 18th and 19th centuries, the author recounts the circumstances which took them to the pinnacle of British political life, probes their political and personal strengths and weaknesses, assesses their performance in office and asks what lasting influence they have had. Along the way Leonard entertains and informs, revealing little-known facts about the private lives of each of the Prime Ministers such as who was suspected to be an illegitimate half-brother of George III, who was assassinated in the House of Commons, and who spent his evenings prowling the streets of London , trying to 'reform' prostitutes. This book can also form part of a two-volume set published by Routledge including the companion volume Modern British Prime Ministers from Balfour to Johnson. This book will be of key interest to scholars, students and readers of British political history, the Executive, Government, and British Politics"--